On the role of financial aid in a default episode - Gabriel Cuadra; Manuel Ramos-Francia; Santiago García-Verdú (Banco de México, 2018)
We develop a dynamic stochastic quantitative model of sovereign default featuring fiscal policy, endogenous financial aid and risk-averse foreign lenders, in order to explore the role of financial aid in a default episode. After calibrating the model, we feed output shocks into the model to show that it captures some of the most salient features of the fiscal and debt situation in Argentina during the 1998-2002 period. This underscores the economic nature of the decision to default and the role that official aid could have taken in avoiding such an event. In effect, given the economic challenges endured by Argentina, a full-fledged default took place. In addition, we discuss a number of policy implications associated with financial aid programs aimed at preventing sovereign default episodes.
Keywords: E62; F34; 330; Sovereign default; fiscal policy; financial aid